The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3928/1081597x-20160602-01
|View full text |Cite
|
Sign up to set email alerts
|

Lower Energy Levels Improve Visual Recovery in Small Incision Lenticule Extraction (SMILE)

Abstract: An energy level close to the plasma threshold during SMILE provides a faster and better visual recovery. [J Refract Surg. 2016;32(9):636-642.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 18 publications
3
16
1
Order By: Relevance
“…32,33 The initial light scattering and blurring in SMILE may be related to interface irregularities; hence a smooth lenticule dissection is important for the visual outcome 34 together with continuous optimization of the femtosecond laser energy settings. 35 It is important to note that we did find similar postoperative visual symptoms 3 months after surgery, although significantly different levels of light scattering can be present up to 6 months after LASIK and SMILE. 32,33 Although a randomized, paired-eye, patient-masked study allows for the most objective comparison between eyes with regard to a patient's subjective experience, our study still has some limitations.…”
Section: Discussionsupporting
confidence: 57%
“…32,33 The initial light scattering and blurring in SMILE may be related to interface irregularities; hence a smooth lenticule dissection is important for the visual outcome 34 together with continuous optimization of the femtosecond laser energy settings. 35 It is important to note that we did find similar postoperative visual symptoms 3 months after surgery, although significantly different levels of light scattering can be present up to 6 months after LASIK and SMILE. 32,33 Although a randomized, paired-eye, patient-masked study allows for the most objective comparison between eyes with regard to a patient's subjective experience, our study still has some limitations.…”
Section: Discussionsupporting
confidence: 57%
“…[J Refract Surg. 2018;34(1): [11][12][13][14][15][16] 13,14 have suggested that lower energy resulted in improved healing after SMILE. More studies are needed about the independent relationship between energy setting and the postoperative visual outcome in SMILE.…”
Section: Discussionmentioning
confidence: 99%
“…However, low energy in the range of our study did not cause more difficulties than high energy. Although some studies also showed that increased energy leads to easier dissection of the lenticule, 14 others examined the disadvantages of using high energy. Netto et al 19 reported that higher energy in rabbits could induce an inflammatory response and may be responsible for the early blurred vision in femtosecond laser-assisted LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison with other studies, a literature review was performed to find all reports of suction loss in SMILE. Twenty-two studies were identified and the suction loss incidence is summarized in Table 5 Wang et al 2013Wang et al , 2014Wang et al , 2017Ganesh & Gupta 2014;Ivarsen et al 2014;Sekundo et al 2014;Wong et al 2014, Kamiya et al 2015Ramirez-Miranda et al 2015;Xu & Yang 2015;Donate & Thaeron 2016;FDA, 2016;Liu et al 2016;Osman et al 2016;Pradhan et al 2016;Yildirim et al 2016; Gab-Alla 2017; Park & Koo 2017;Pedersen et al 2017;Taneri et al 2017;Titiyal et al 2017;Damgaard et al 2018). For studies with large populations of more than 1500 procedures (Ivarsen et al 2014;Liu et al 2016;Osman et al 2016;Pradhan et al 2016;Park & Koo 2017;Wang et al 2017), the incidence was similar to the 0.50% in the current study, ranging from 0.17% (Pradhan et al 2016) to 0.20% (Park & Koo 2017), 0.41% (Liu et al 2016), 0.78% (Ivarsen et al 2014), up to 0.93% (Wang et al 2017), and a highest value of 2.10% (Osman et al 2016).…”
Section: Discussionmentioning
confidence: 99%